PENGUKURAN DEBIT AIR DAN MUATAN SUSPENSI DI SUB DAS BAKARANGAN DESA BAKARANGAN KECAMATAN KUSAN HULU KABUPATEN TANAH BUMBU KALIMANTAN SELATAN - Awaludin Awaludin; Muhammad Ruslan; Karta Sirang (Jurnal Sylva Scienteae, 2020)
Measurement of Water Debit and Suspension Load In Bakarangan Bakarangan Sub-Basin Sub-District Kusan Hulu District Tanah Bumbu Regency South Kalimantan. Guided by Prof. Dr. Ir. H.Muhammad Ruslan, M.S and Mr. Ir. Karta Sirang, M. Objective of this research is to know the amount of water debit and the suspension load on Kusan River in Sub Das Bakarangan of Tanah Bumbu and Regency to know the relationship between water discharge and suspension load on Kusan river in Sub Das Bakarangan Tanah Bumbu Regency. The method used by measuring the water debit and the suspension charge of Sub Das Bakarangan, the data is processed and analyzed and then described. The result of this research is the biggest water discharge happened on October 5, 2017 equal to 4,715 m³ / sec with average water level 1.78 m while minimum water discharge happened on October 19, 2017 equal to 2,815 m³ / sec with average height water level 1.53 m. The largest suspended load occurred on October 12, 2017 of 0.255 gr / lt with a suspended charge discharge of 0.0748 tons / day. While the smallest loaded content contents occurred on November 9, 2017 of 0.100 gr / ltr with a discharge charge of 0.0251 ton / day. The regression equation produced between the water level (x) and the suspension charge (y) ie y = 5.8665x-5.7784 has a strong correlation (r) relationship of 0.7817. The regression equation produced between the water level and the suspended charge ie y = 0.0472x-0.0105 has a strong correlation (r) relationship of 0.0588. The regression equation generated between the water discharge (x) and the suspended charge discharge (y) ie y = 0.004x + 0.0733 has a strong correlation (r) relationship of 0.9134.Keywords: watershed; water discharge; suspension charge